New eriophyoid mites (Acari: Prostigmata: Eriophyoidea) from banana and heliconia in Northeastern Brazil—two new genera and three new species - Reis, Aleuny C.; Gondim Jr., Manoel G. C.; Navia, Denise; Flechtmann, Carlos H. W. (Zootaxa, 2011)
A new genus and new species of the mite family Eriophyidae (Phyllocoptinae), namely Cothrix erugata n. sp. et n. gen., is described from Heliconia stricta Huber (Heliconiaceae). In addition, one new genus and two new species of Diptilomiopidae, namely Rhyncadicrus asperulus n. sp. et n. gen. from banana, Musa acuminata Colla x Musa balbisiana Colla (genomic group AAB) (Musaceae) and Catarhinus granatus n. sp. from Heliconia bihai L., are described and illustrated. The mites were collected in the State of Pernambuco, Northeastern Brazil. All were vagrants on the lower leaf surfaces of their host plants and no visible damage symptoms were observed.